Pablo's Self-Serve Food Ordering System with Virtual Waitlist Management - Jo, Jonathan; Hamzah, Mohd Hamdi Irwan Bin Hamzah (Applied Information Technology And Computer Science, 2024)
Pablo's restaurant at 49 Bishop Street in George Town, Malaysia, is revolutionising dining with its "Pablo's Self-Serve Food Ordering System with Virtual Waitlist Management." This project introduces a web-based solution to improve operational efficiency and customer satisfaction by eliminating the existing system's long wait times and poor order handling. Its main objectives are to develop, build, and test an enhanced meal ordering and virtual waiting list system. PHP and MySQL were used to build the agile, object-oriented system. Its mobile-responsive digital menu and Order Progression Bar allow customisable ordering and live tracking. The system improves restaurant efficiency by improving order processes and communication. Future upgrades will focus on refining the ordering process to maintain Pablo's restaurant competitive advantage. This complete approach ensures Pablo's leadership in innovation, customer satisfaction, and operational excellence.